Knowledge, attitude and practice study about HPV and its vaccination among medical college students in North India - Kumar, Amit; Garg, Paridhi (International Journal of Advances in Medicine, 2020)
Background: Cervical cancer is one of the most important cancers in women. Cervical cancer is primarily caused by sexually transmitted human papilloma virus (HPV) infection. It has been proven that HPV vaccination, preferably before initiation of sexual life, is highly effective in HPV and cervical cancer prevention. So, this study was conducted to study the knowledge, attitude and practice about the significance of HPV and its vaccination among medical students. Methods: This was a cross-sectional observational study conducted in a medical college. 200 medical students were requested to fill a questionnaire which covered demographic details, knowledge, attitude and practice towards HPV vaccination for cervical cancer prevention. Results: Majority of the students knew that HPV may cause cancer in humans (94%), leading to cervical cancer in females (84.5%) and about the availability of its vaccine in India (79%). But only a few students were aware that it may even lead to cancer in males (52.5%), knew the correct dosing schedule (60%) and that even vaccinated female may develop cancer (36.5%). 74.5% considered its vaccine to be safe, 71.5% considered it effective and 68% considered it protective against sexual partner. Only 33.5% were vaccinated but 92.5% said that they would recommend HPV vaccine to their family. Conclusions: Though the knowledge and attitude about the significance of HPV and its vaccination is good among the medical college students, but the practice of vaccination is poor.